3x4 - 288x2 - 1200 = 0
Steps 1 and 2
All three terms are already on the left side of the equation, so we may begin factoring. First, we factor out a greatest common factor of 3.
3(x4 - 96x2 - 400) = 0
Next, we factor a trinomial.
3(x2 + 4)(x2 - 100) = 0
Finally, we factor the binomial (x2 - 100) as a difference between two squares.
3(x2 + 4)(x + 10)(x - 10) = 0
We proceed by setting each of the four factors equal to zero, resulting in four new equations.
1. 3 = 0
The first equation is invalid, and does not yield a solution. The second equation cannot be solved using basic methods. (x2 + 4 = 0 actually has two imaginary number solutions, but we will save Imaginary Numbers for another lesson!) Equation 3 has a solution of x = -10, and Equation 4 has a solution of x = 10.
We now include all the solutions we found in a single solution to the original problem:
x = -10, 10
This may be abbreviated as
x = ??10